Gestão do conhecimento e recursos humanos em bibliotecas universitárias brasileiras e portuguesas - Marques Júnior, Euro; Albino, João Pedro [UNESP] (My University, 2011)
The Knowledge Management represents a new vision of management of organizations, since information and knowledge are the main factors of competitiveness, today, of individuals, organizations and nations. The university plays a key role alongside with government and industry in the generation of technological innovations that can help the society progress, and the University Library is an important disseminator of scientific information. The main challenges of organizations involved in Knowledge Management are concentrated in the management of cultural and behavioral changes of its human resources and in creating an environment conducive to create, use and share information and knowledge. Within this context the question arises: How do University Libraries in Brazil and Portugal employ people management and knowledge management in order to improve the quality of its services and the productivity of their institutions? To answer it we developed a descriptive-analytic research, using the method of comparative study, analyzing 69 organizations. According to the survey results, the people management issues were the worst assessed in relation to other aspects of Knowledge Management, showing a weak dissemination of these practices in the University Libraries of Brazil and Portugal and the great need for initiatives to help develop them.

A Gestão do Conhecimento (GC) representa uma nova visão da gestão das organizações, uma vez que a informação e o conhecimento são os principais fatores de competitividade, hoje, de indivíduos, organizações e nações. A universidade tem um papel fundamental, juntamente com o governo e a indústria na geração de inovações tecnológicas que podem alavancar o progresso da sociedade, tendo a Biblioteca Universitária (BU) como uma disseminadora de informações científicas importantes. Os principais desafios das organizações envolvidas na GC estão concentrados na gestão de mudanças culturais e comportamentais de seus recursos humanos e na criação de um ambiente propício para criar, usar e compartilhar informações e conhecimento. Dentro deste contexto surge uma pergunta: Como as Bibliotecas Universitárias no Brasil e em Portugal empregam a Gestão do Conhecimento a fim de melhorar a qualidade de seus serviços e a produtividade de suas instituições? Para respondê-la desenvolveu-se uma pesquisa descritivo-analítica, utilizando o método de estudo comparativo, analisando 69 organizações. De acordo com os resultados da pesquisa, as questões ligadas à gestão de pessoas foram pior avaliadas em relação a outros aspectos da GC, mostrando uma fraca disseminação destas práticas nas BUs do Brasil e de Portugal e a grande necessidade de iniciativas que ajudem a desenvolvê-las.
The knowledge management and human resources in brazilian and portuguese university libraries
Keywords: Knowledge management; Human resources; People management; University library; Gestão do conhecimento; Recursos humanos; Gestão de pessoas; Biblioteca universitária